Dinâmica de circulação e distribuição da infecção por Yersinia pestis em cães e gatos nos focos de peste do estado do Ceará - Sousa, Larissa Leão Férrer de (2017)
Introduction: Plague is a zoonosis of historical importance, making it one of the oldest diseases known and feared by humanity. It continues to occur in many regions of the world and remains in nature through an intricate and complex epidemiological chain formed especially by rodents and their fleas and other mammals. In Brazil, there are plague outbreaks with persistent bacterial circulation, with Ceará being of great importance in the epidemiological context of the disease, with annual human cases and positivity of sentinel animals in focus areas. Objective: To characterize the circulation and distribution dynamics of Y. pestis infection in domestic carnivores (dogs and cats) evaluated by the Plague Control Program (PCP) of the seven plague foci areas of the State of Ceará. Methods: Ecological study of the temporal series type, in which secondary data of domestic carnivores of the Pest areas belonging to the state of Ceará were analyzed. Data salvage of the Pest Information System (SISPESTE) and laboratory results from the Regional Pest Laboratory in Fortaleza (1997 to 2005) and the Public Health Laboratory (LACEN) of the State of Ceará (2005 to 2014). Data were analyzed using Stata software (version 11.2) and the Joinpoint program. Results: In the serological survey in plague outbreaks in Ceará, it showed positive results with similar indexes in dogs and cats. The reduction in prevalence in domestic cats was significant from 2007, explained by the paralysis of the serology in cats from the year 2010. Conclusion: The study shows the bacterium Y. pestis present and in active circulation in all the pestígenas areas of the state . Plague has shown a tendency to decrease positivity in carnivores. It is recognized that dogs and cats (domestic carnivores) participate in the epidemic cycle of plague and with active circulation of the bacteria active in the areas of plague outbreaks.